Die komplementäre Wirkung von unternehmerischer Orientierung, Marktorientierung und Lernorientierung auf den Unternehmenserfolg junger Technologieunternehmen - Deutscher, F; Schwens, C; Zapkau, F B; Kabst, Rüdiger

Multitouch-, Be-Greifbare- und Stiftbasierte-Interaktion in der Einsatzlageplanung - Nebe, Karsten; Fischer, Holger Gerhard; Klompmaker, Florian; Jung, Helge (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

Authentifizierte Eingaben auf Multitouch-Tischen - Jung, Helge; Nebe, Karsten; Klompmaker, Florian; Fischer, Holger Gerhard (Mensch & Computer 2011, 11. fachübergreifende Konferenz für interaktive und kooperative Medien, überMEDIEN - ÜBERmorgen)

A Holistic Model for Integrating Usability Engineering and Software Engineering Enriched with Marketing Activities - Fischer, Holger Gerhard; Nebe, Karsten; Klompmaker, Florian (Human Centered Design)

Der Qualitätsstandard für Usability Engineering der German UPA – Aktueller Stand der Arbeiten - Fischer, Holger Gerhard; Bogner, Christian; Geis, Thomas; Polkehn, Knut; Zimmermann, Dirk (Jahresband Usability Professionals)

Disentangling the Effect of Prior Entrepreneurial Exposure on Entrepreneurial Intention – An empirical Analysis based on the Theory of Planned Behavior - Zapkau, F B; Schwens, C; Steinmetz, Holger; Kabst, Rüdiger

The influence of entrepreneurial traits on the strategic orientation and new product success in high-technology firms - Maekelburger, B; Zapkau, F B; Kabst, Rüdiger

Methodology of the Cranet Survey - International Executive Report 2011, Cranfield - Kabst, Rüdiger; Wehner, M C

Innovative Lehrkräfte- und Schulentwicklung. Das Wirtschaftspädagogische Graduiertenkolleg der Universität Paderborn - Sloane, Peter F. E.; Kremer, H.-Hugo; Krakau, U. (Wirtschaft und Erziehung)

Vorteile der Paketbildung in Verhandlungen: Ein prozeduraler Zugang zu Superadditivität - Diehl, Matthias

Bidirectionally Coupled Network and Road Traffic Simulation for Improved IVC Analysis - Sommer, Christoph; German, Reinhard; Dressler, Falko (IEEE Transactions on Mobile Computing)
Recently, many efforts have been made to develop more efficient Inter-Vehicle Communication (IVC) protocols for on-demand route planning according to observed traffic congestion or incidents, as well as for safety applications. Because practical experiments are often not feasible, simulation of network protocol behavior in Vehicular Ad Hoc Network (VANET) scenarios is strongly demanded for evaluating the applicability of developed network protocols. In this work, we discuss the need for bidirectional coupling of network simulation and road traffic microsimulation for evaluating IVC protocols. As the selection of a mobility model influences the outcome of simulations to a great deal, the use of a representative model is necessary for producing meaningful evaluation results. Based on these observations, we developed the hybrid simulation framework Veins (Vehicles in Network Simulation), composed of the network simulator OMNeT++ and the road traffic simulator SUMO. In a proof-of-concept study, we demonstrate its advantages and the need for bidirectionally coupled simulation based on the evaluation of two protocols for incident warning over VANETs. With our developed methodology, we can advance the state-of-the-art in performance evaluation of IVC and provide means to evaluate developed protocols more accurately.

User-space Scheduling for Heterogeneous System under Linux - Welp, Daniel

Towards Systematic, Comprehensive Trace Generation for Behavioral Pattern Detection through Symbolic Execution - von Detten, Markus (Proceedings of the 10th ACM SIGPLAN/SIGSOFT Workshop on Program Analysis for Software Tools and Engineering (PASTE))
In reverse engineering, dynamic pattern detection is accomplished by collecting execution traces and comparing them to expected behavioral patterns. The traces are collected by manually executing the program in question and therefore represent only part of all relevant program behavior. This can lead to false conclusions about the detected patterns. In this paper, we propose to generate all relevant program traces by using symbolic execution. In order to reduce the created trace data, we allow to limit the trace collection to a user-selectable subset of the statically detected pattern candidates.

Stabilizing consensus with the power of two choices - Doerr, Benjamin; Goldberg, Leslie Ann; Minder, Lorenz; Sauerwald, Thomas; Scheideler, Christian (Proceedings of the 23rd ACM Symposium on Parallelism in Algorithms and Architectures (SPAA))
In the standard consensus problem there are n processes with possibly di®erent input values and the goal is to eventually reach a point at which all processes commit to exactly one of these values. We are studying a slight variant of the consensus problem called the stabilizing consensus problem [2]. In this problem, we do not require that each process commits to a ¯nal value at some point, but that eventually they arrive at a common, stable value without necessarily being aware of that. This should work irrespective of the states in which the processes are starting. Our main result is a simple randomized algorithm called median rule that, with high probability, just needs O(logmlog log n + log n) time and work per process to arrive at an almost stable consensus for any set of m legal values as long as an adversary can corrupt the states of at most p n processes at any time. Without adversarial involvement, just O(log n) time and work is needed for a stable consensus, with high probability. As a by-product, we obtain a simple distributed algorithm for approximating the median of n numbers in time O(logmlog log n + log n) under adversarial presence.

Weblogs zur Unterstützung der Theorie-Praxis-Integration in der Wirtschaftslehrenden-Ausbildung - Jenert, Tobias; Gebhardt, Anja; Käser, Reto (Zeitschrift für E-Learning)
Eine zentrale Herausforderung in der Ausbildung angehender Wirtschaftslehrpersonen stellt die sinnvolle Verknüpfung von Theorie- und Praxiserfahrungen dar. Im Rahmen der Ausbildung angehender Wirtschaftslehrpersonen an der Universität St. Gallen wird eine Lernumgebung gestaltet, die eine Verschränkung von Theorie- und Praxiserfahrungen ermöglichen soll. Die Lernprozesse der Studierenden werden dabei durch didaktisch angeleitete Weblogarbeit unterstützt. Trotz der Lernchancen, die sich aus einer Verknüpfung von theoretischen und praktischen Lernphasen ergeben, schätzen die Studierenden den Nutzen der Weblogarbeit als äusserst gering ein. Die Studierenden bei der reflexiven Integration praxisnaher und theoretischer Lernerfahrungen zu unterstützen, ist eine Herausforderung, die dezidierter Anleitung und Förderung durch die Lehrpersonen bedarf
Keywords: Weblog; Blog; e-learning; TEL; higher education; business education

Die Studierenden? - Ein sozio-kultureller Blick auf das Studieren in Bologna-Strukturen - Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Die hochschulbezogene Lernforschung konzentierte sich bislang vor allem auf das Lernen Studierender im Vorlesungssaal (Classroom Learning). Im Zuge der Bologna-Diskussion stellt sich jedoch vermehrt die Frage, wie Studierende den langfristigen Bildungspfad eines ganzen Studiums gestalten. Denn obschon Studierende seit langem Gegenstand der Forschung sind, ist bislang wenig dazu bekannt, wie Lernaktivitäten ausgewählt und Ressourcen im Studium verteilt werden. Der Beitrag nimmt diese Frage auf und untersucht, welche Handlungsstrategien Studierende bei der Bewältigung ihres Studienalltags in unterschiedlichen Bologna-konformen Studienprogrammen entwickeln und welche Rahmenbedingungen dabei eine Rolle spielen.
Keywords: Programmentwicklung; Bologna; Studierende; Kulturpsychologie; Studienprogramm

Studierendenorientierung: Wege und Irrwege eines Begriffs mit vielen Facetten - Reinmann, Gabi; Jenert, Tobias (Zeitschrift für Hochschulentwicklung)
Studierendenorientierung ist derzeit eines der Leitkonzepte für die Gestaltung der Lehre an Hochschulen. Ein kritischer Blick offenbart jedoch, dass der Begriff uneinheitlich und mit teils widersprüchlichen Konnotationen gebraucht wird. Der Beitrag analysiert die Begriffsverwendungen innerhalb verschiedener Hochschulkontexte. Dabei werden Widersprüche zwischen den vorgefundenen Konnotationen - insbesondere zwischen den Perspektiven des Hochschulmanagements und der Didaktik - identifiziert. Davon ausgehend wird mit dem Konzept der Bildungsorientierung eine Alternative vorgeschlagen, die auf das Kernziel der Hochschule als Bildungsorganisation verweist und die skizzierten Unschärfen vermeidet.
Keywords: Studierendenorientierung; Hochschulmanagement; Hochschuldidaktik

Developing a learning centered model for designing and managing study programmes - Jenert, Tobias
Research on teaching and learning in higher education has first and foremost centered on individuals, i.e. students' and teachers' approaches to learning and teaching as well as methods (Entwistle, McCune, & Scheja, 2006; Entwistle & Peterson, 2004). As a consequence, concepts on how to improve and innovate education at higher education institutions (HEI) have stayed on the level of individual courses, trying to qualify teachers to implement new teaching and learning methods in their classrooms (Aineley, 2008, S. 619). Yet, there are both theoretical as well as practical reasons that argue for a broader perspective on learning processes and, as a consequence, reach beyond the course-level but focus on entire educational programmes instead: First, over the last thirty years or so, learning theories are increasingly stressing the importance of (a) social-material contexts (McInerney & van Etten, 2002) as well as (b) learners' subjective experiences. This suggests that a course of study be not regarded as a mere addition of more or less independent courses, but rather as a holistic learning experience. This includes the sum total of a student's educationally purposeful social-material interactions at a HEI both within and outside the classroom (cf. Hu & Kuh, 2002). A second, more practical reason why educational researchers and designers should take a closer look on the design of educational programmes lies in the Bologna process: The introduction of the European Credit Transfer System as well as the tow-tiered study structure force HEI to systematically craft their programmes' internal structure. Due to the fact that there are virtually no pedagogical concepts concerning the design of study programmes, these design processes have so far been dominated by administrative considerations, largely neglecting students' experiences within the programme structures (Winter, 2009; Hildbrand, Tremp, Jäger & Tückmantel, 2008). Thus, it can be concluded that there is a lack of knowledge on how distinctive design features of study programmes (1) are perceived by students and (2) impact on their action strategies concerning for example the selection of learning activities, the attribution of resources for learning, and social interactions with their peers.
Keywords: educational development; study programmes; approaches to studying

Learning culture as a prerequisite for an institution-wide approach to educational development - Brahm, Taiga; Gebhardt, Anja; Jenert, Tobias
Over the last two decades, the discussion about innovating teaching and learning at higher education institutions (HEI) has concentrated on various core concepts: such as an increased focus on learning outcomes as competencies and more student-centered teaching. These concepts form part of what Barr and Tagg (1995) have termed the "shift from teaching to learning". However, very few approaches have been proposed so far in the scholarly literature on how to actually transfer such normative concepts into the practice of teaching and learning at HEI. In order to sustainably develop the practices of teaching and learning at HEI, it is necessary to comprehend the prerequisites for educational development. The construct of "learning culture" can be seen as a possible concept to explicate these prerequisites. The aims of this study are to (a) propose an institution-wide approach to educational development at HEI and to (b) present a comprehensive instrument to diagnose learning culture as a starting point for educational development. The findings of the study include a first version of the Learning Culture Inventory for HEI. The students' version of the instrument encompasses 12 scales for the individual, 12 for the pedagogical interactions and 5 for the organizational dimension. The assumed basic factor structure of the instruments could be confirmed. With the institution-wide approach to educational development and the Learning Culture Inventory, this study can provide the basis for sustainable developmental initiatives to innovate teaching and learning at HEI.
Keywords: higher education; instrument development; strategy; educational development

Fertigkeiten und Einstellungen Studierender zum Bloggen in Praxisprojekten oder: Spannungsfelder und Teufelskreise beim selbstorganisierten Lernen - Gebhardt, Anja; Jenert, Tobias
Der Beitrag untersucht die Weblog-Arbeit Studierender zur Dokumentation und Reflexion von Praxisprojekten. Zu Beginn und nach Abschluss einer Lehrveranstaltung mit Praxisphase wurden Studierende zur Weblog-Arbeit befragt. Es zeigt sich, dass die Studierenden kaum über Erfahrungen in der Nutzung von Weblogs verfügen und überwiegend negative Einstellungen zum Bloggen aufweisen. Die Blogeinträge erreichen nicht die angestrebte Reflexionstiefe. Es wird diskutiert, wie das didaktische Design gestaltet werden kann, um die gewünschten Effekte ‒ Peer-Feedback und tiefgehende Reflexion ‒ zu erreichen.
Keywords: Weblog; Selbststudium; Praxisprojekte; Selbstorganisiertes Lernen